Survey of Cardiovascular Endurance Levels of Smoker and Non-Smoking Football Athletes (Gawang FCC Tumpang Malang Regency) - Rhama Fauzi Affandi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research aims to determine the cardiovascular endurance of smoking and non-smoking football athletes which can be used as information for coaches or athletes in implementing lifestyle and exercise patterns. The research method used is quantitative descriptive without testing a particular hypothesis. The instruments used are tests and measurements using the Bleep Test. The results obtained showed that there were 3 (30%) athletes in the good category, and 7 (70%) athletes in the medium category. The results of cardiovascular tests on non-smoking players at the Gawang FCC Tumpang, Malang Regency, were that there were 3 (30%) athletes in the very good category, 6 (60%) athletes in the good category, and 1 (10%) athlete in the fair category. So it is recommended that trainers to pay more attention to improving cardiovascular endurance when preparing training programs without neglecting technical or tactical training. Meanwhile, football athletes should use these results as a guide and tool to motivate themselves to have better cardiovascular endurance and avoid things that can damage their body's health, especially smoking.